Comparison of survival analysis and palliative care involvement in patients aged over 70 years choosing conservative management or renal replacement therapy in advanced chronic kidney disease. (October 2013) - Hussain, Jamilla A; Mooney, Andrew; Russon, Lynne
Background: There are limited data on the outcomes of elderly patients with chronic kidney disease undergoing renal replacement therapy or conservative management. Aims: We aimed to compare survival, hospital admissions and palliative care access of patients aged over 70 years with chronic kidney disease stage 5 according to whether they chose renal replacement therapy or conservative management. Design: Retrospective observational study. Setting/participants: Patients aged over 70 years attending pre-dialysis clinic. Results: In total, 172 patients chose conservative management and 269 chose renal replacement therapy. The renal replacement therapy group survived for longer when survival was taken from the time estimated glomerular filtration rate <20 mL/min ( p < 0.0001), <15 mL/min ( p < 0.0001) and <12 mL/min ( p = 0.002). When factors influencing survival were stratified for both groups independently, renal replacement therapy failed to show a survival advantage over conservative management, in patients older than 80 years or with a World Health Organization performance score of 3 or more. There was also a significant reduction in the effect of renal replacement therapy on survival in patients with high Charlson's Comorbidity Index scores. The relative risk of an acute hospital admission (renal replacement therapy vs conservative management) was 1.6 ( p < 0.05; 95% confidence interval = 1.14–2.13). A total of 47% of conservative management patients died in hospital, compared to 69% undergoing renal replacement therapy (Renal Registry data). Seventy-six percent of the conservative management group accessed community palliative care services compared to 0% of renal replacement therapy patients. Conclusions: For patients aged over 80 years, with a poor performance status or high co-morbidity scores, the survival advantage of renal replacement therapy over conservative management was lost at all levels of disease severity. Those accessing a conservative management pathway had greater access to palliative care services and were less likely to be admitted to or die in hospital.